A COMPARATIVE ANALYSIS OF DESARDA TISSUE REPAIR VERSUS LICHTENSTEIN MESH HERNIOPLASTY IN THE MANAGEMENT OF INGUINAL HERNIA - ASMA AZIM; PATEL, RAHUL; SINGH, PIYUSH; ASHWITHA CRASTA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Inguinal hernia repair is among the most frequently performed surgical procedures worldwide. While the Lichtenstein mesh hernioplasty remains the gold standard, it carries risks such as infection, chronic pain, and foreign body complications. Desarda tissue repair, a mesh-free technique, has emerged as a potential alternative, claiming advantages including reduced complications and faster recovery. This study aims to compare clinical outcomes, post-operative pain, complications, and recovery times between Desarda tissue repair and conventional Lichtenstein mesh hernioplasty. Methods: This comparative study was conducted at People’s Hospital, Bhopal. Following ethical clearance and informed consent, 82 patients meeting the inclusion criteria were enrolled from March 2023 onward. Participants were divided into two groups: one undergoing Desarda tissue repair and the other receiving Lichtenstein mesh hernioplasty. Parameters such as duration of surgery, post-operative pain (Visual Analog Scale [VAS] score), complications, hospital stay, and time to return to normal activity were assessed and compared. Data were analyzed using the Statistical Package for the Social Sciences version 26.0. Results: Desarda tissue repair demonstrated significantly superior outcomes compared to Lichtenstein mesh hernioplasty. It was associated with reduced operative time, faster recovery, shorter hospital stay, and notably lower postoperative pain (mean VAS score: 2.76±2.02 vs. 4.88±2.66; p=0.03). In addition, Desarda repair showed fewer complications, with no instances of wound infection, seroma, chronic pain, or sensory loss. The incidence of overall complications was significantly lower in the Desarda group (97.56% complication-free vs. 73.17% in the mesh group; p=0.02). Conclusion: Desarda tissue repair is a safer and more effective alternative to Lichtenstein mesh hernioplasty for inguinal hernia management. Its association with reduced operative and recovery times, fewer complications, and lower post-operative pain supports its use, especially in patients seeking mesh-free surgical options.